Carcass wrote:

If

r > 0, s ≠

\frac{1}{2} and

r = \frac{3s +1}{1-2s}, then

s=A)

\frac{3r}{12 +6r}B)

\frac{-2r}{3}C)

\frac{r-1}{3+2r}D)

\frac{2}{3(1-r)}E)

\frac{-1+r}{3}Given:

r = \frac{3s +1}{1-2s}Multiply both sides by (1 - 2s) to get: r(1 - 2s) = 3s + 1

Expand: r - 2rs = 3s + 1

NOTE: We want the s's on one side. So....

Add 2rs to both sides: r = 3s + 2rs + 1

Subtract 1 from both sides: r - 1 = 3s + 2rs

Factor right side: r - 1 = s(3 + 2r)

Divide both sides by (3 + 2r) to get: (r - 1)/(3 + 2r) = s

Answer:

Cheers,

Brent

_________________

Brent Hanneson – Founder of greenlighttestprep.com

Check out the online reviews of our course